Academic Stress in First-Year Biology Education Students: The Role of Coping Strategies and Self-Esteem - Jajang Miharja; Rukun Maulana Sidik; Indra Darmawan; Solihin Solihin (Journal Of Biology Education Research (JBER), 2026)
First-year university students frequently experience academic stress as they adapt to new academic, social, and personal demands. Excessive academic stress may adversely affect students’ psychological well-being, self-esteem, and academic performance. Therefore, understanding the roles of coping strategies and self-esteem is important for identifying factors associated with academic stress among first-year students. This study aimed to examine the relationships among coping strategies, self-esteem, and academic stress among first-year biology education students. A quantitative correlational design was employed involving 22 first-year biology education students selected through purposive sampling. The study investigated three variables, namely coping strategies, self-esteem, and academic stress, without administering any intervention or treatment. Data were collected using standardized questionnaires measuring coping strategies, self-esteem, and academic stress. Pearson correlation analysis was conducted to examine the relationships between coping strategies and academic stress as well as between self-esteem and academic stress, while multiple correlation analysis was used to determine the combined relationship of coping strategies and self-esteem with academic stress. The results demonstrated a significant negative relationship among coping strategies, self-esteem, and academic stress, indicating that students with more effective coping strategies and higher levels of self-esteem tended to report lower levels of academic stress. These findings suggest that coping strategies and self-esteem are important psychological factors associated with academic stress among first-year university students and should be considered in developing programs to support students’ psychological adjustment and academic success during the transition to higher education.